2017
DOI: 10.1053/j.ajkd.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Family Aggregation and Heritability of ESRD in Taiwan: A Population-Based Study

Abstract: This whole population-based family study in Asia confirmed, in a Taiwanese population, that a family history of ESRD is a strong risk factor for this disease. Moderate heritability was noted and environmental factors were related to disease. Family history of ESRD is an important piece of clinical information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 35 publications
2
37
0
Order By: Relevance
“…However, the magnitude of this risk varied across races, with the highest risk reported among Asian and black donors in comparison to white donors. Although these findings in Asian donors are in line with the study from Taiwan, 10 we would caution the readers regarding the accuracy of actual risk estimates due to the small number of donors. After excluding identical twins among biologically related donor-recipient pairs, the authors found that black donors (particularly first-degree relatives) experienced a higher risk for ESKD compared with white donors.…”
supporting
confidence: 80%
“…However, the magnitude of this risk varied across races, with the highest risk reported among Asian and black donors in comparison to white donors. Although these findings in Asian donors are in line with the study from Taiwan, 10 we would caution the readers regarding the accuracy of actual risk estimates due to the small number of donors. After excluding identical twins among biologically related donor-recipient pairs, the authors found that black donors (particularly first-degree relatives) experienced a higher risk for ESKD compared with white donors.…”
supporting
confidence: 80%
“…U.S. Renal Data System Annual Data Report (USRDS) recently claims, about 450 per million populations in Taiwan suffered by End-Stage Renal Disease (ESRD) and its incidence prevalence became most common among the highest in the world [ 1 ]. Taiwan Renal Registry Data System (TWRDS) confirmed the fact that, recently more than 80,000 Taiwanese patients are dialysis urgency and the count is growing [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Taiwan, ESA can only be initiated in CKD patients with a serum creatinine higher than 6 mg/dL according to the National Health Insurance policy, and the use of this feature to identify non-dialysis stage 5 CKD patients in Taiwan have been found to be very accurate by others (Hsau et al, 2014 ; Shih et al, 2014 ; Hung et al, 2015 ). The identification of those with end-stage renal disease under chronic dialysis, or stage 5D CKD patients, also followed the approach detailed in the existing literature, based on the presence of ICD-9-CM code 585.6 and the co-existence of official certificates of having end-stage renal disease under chronic dialysis, issued by the National Health Insurance Bureau of Taiwan (Chao et al, 2017 ; Lin et al, 2017 ; Wu et al, 2017a ). The official certificates are called “catastrophic illness certificate,” serving as a firm proof of the patients' disease status, and are regularly audited and maintained in governmental database (called “Registry of Catastrophic Illness Database”) (Lin et al, 2014 , 2017 ; Wu et al, 2017a ).…”
Section: Methodsmentioning
confidence: 99%